Depressive symptoms in Danish elite athletes using the Major Depressive Inventory (MDI) and the Center for Epidemiological Studies Depression Scale (CES-D) - Kuettel, A.; Melin, A.; Larsen, C. H.; Beck Lichtenstein, M. (Scandinavian Journal of Sport and Exercise Psychology, 2022)
The prevalence of depressive symptoms among athletes is an ongoing debate inthe scientific literature. The aim of the current study was to assess the prevalence of depressive symptoms in Danish elite athletes and to evaluate the psychometric properties of the Major Depressive Inventory (MDI) and the Center for Epidemiological Studies Depression Scale (CES-D) in athletes.The total sample comprised 996 athletes from two cross-sectional studies using the MDI (n= 409) and the CES-D (n= 587). Using the original cut-off points, the MDI found 8.6% and the CES-D found 24.9% at risk of depression. Using alternative cut-off points, both instruments detected 10-11% of athletes at risk. No statistically significant differences were found related to age, injury, and type of sport between high risk and low risk groups, whereas female athletes were overrepresented in the high-risk groups. Principal component analyses confirmed a single factor structure in both instruments with sufficient item loadings on the first component and Cronbach avalues of .89 and .88. We recommend regular screening of depressive symptoms in elite athletes, with MDI and CES-D as valid instruments for that purpose. The appropriateness of using different cut-off points in athletic samples is discussed.